1997
DOI: 10.1021/tx970006a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Dithiocarbamate Inhibition of Apoptosis:  Thiol Oxidation by Dithiocarbamate Disulfides Directly Inhibits Processing of the Caspase-3 Proenzyme

Abstract: Dithiocarbamates (DCs) have been reported to be potent inhibitors of apoptosis in several different model systems, which suggests a target common to the apoptotic machinery. Without further investigation, this has been assumed to reflect an antioxidant activity of the DCs. However, we have recently shown that DCs exert prooxidant effects on T cells [Nobel et al. (1995) J. Biol. Chem. 270, 26202-26208], which are dependent on their transfer of external copper into the cells and can be inhibited by the inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 47 publications
5
78
0
Order By: Relevance
“…An internal apoptosis pathway activated via the cleavage of caspase 9 and 3 is well documented (74,75). Furthermore, previous studies also demonstrated that the mechanism behind caspase 3 activation and apoptosis (76)(77)(78) led to morphological and biochemical changes and the modification of key structural and regulatory proteins by caspase 3 (79,80). During this process, the chromatin becomes highly condensed and fragmented to form micronuclei called apoptotic bodies, in a process referred to as nuclear blebbing (81,82).…”
Section: Discussionmentioning
confidence: 97%
“…An internal apoptosis pathway activated via the cleavage of caspase 9 and 3 is well documented (74,75). Furthermore, previous studies also demonstrated that the mechanism behind caspase 3 activation and apoptosis (76)(77)(78) led to morphological and biochemical changes and the modification of key structural and regulatory proteins by caspase 3 (79,80). During this process, the chromatin becomes highly condensed and fragmented to form micronuclei called apoptotic bodies, in a process referred to as nuclear blebbing (81,82).…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that a critical cysteine group in the active site of the caspases makes them sensitive to thiol oxidation. 41 In order to investigate the means of caspase inactivation in cell lysates from Fas treated Jurkat cells incubated with peroxide, we determined the ability of the thiol reducing agent dithiothreitol (DTT) to restore caspase activity. As Figure 4B demonstrates, incubation of hydrogen peroxide (200 mM) treated lysates from anti-Fas treated Jurkat cells with 100 and 200 mM DTT restores caspase activity.…”
Section: Caspases Are Oxidatively Inactivated During Retinal Cell Deathmentioning
confidence: 99%
“…Whereas cell death under conditions in which the caspase family cannot function has been reported to resemble necrosis rather than apoptosis in several studies (25)(26)(27)(28), a growing body of evidence that apoptotic cell death induced by oxidative stress occurs independently of caspase activation has been accumulated (29 -32). In fact, cells have shown apoptosis-like morphological changes, chromatin condensation and/or DNA fragmentation without caspase activation in these papers, suggesting that these distinctive characteristics of apoptosis take place in a caspase-independent manner.…”
mentioning
confidence: 99%